(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2023)
The study analyzes the appropriations about the configurations of competences in the formation of Bachelors in Physical Education (PE). The systematic review was a methodological tool and after selecting the data we reached 13 articles that data analysis points out that although there are few publications on the subject of competences in higher education in PE is a subject that worries many due to the evident neglect regarding the materialization of knowledge in a practical situation. We recognize a certain negligence in the field of leisure and the prevalence of competences related to health. Therefore, we defend an egalitarian, isonomic and equivalent treatment between the areas of leisure, sport and health in the formation of the competences of the bachelor in PE. The diversity of formation needs to be considered, meeting the demands demanded by society, whether in its different public or private work environments.